Bacterial epidemiology of post-operative infections at a cardiac center - Nagamani, Rambhala (International Journal of Research in Medical Sciences, 2016)
Background: Cardiac patients belong to a different group in microbiological perspective as infection causing organisms are different from infection causing pathogens in other patients. Postoperative infections in this group are mainly sternal wound infections and blood stream infections. The present study involved patients from a cardiac center in eastern province, Saudi Arabia, who underwent surgery during a 2 years period. Methods: All positive culture results from cardiac center were collected during this period and data noted. Data included patient demographics, type of surgery/procedure, infection site, infecting organism and the same was analyzed. Results: A total of 4891 patients underwent surgery/procedure at this center during the study period. Overall infection rate was 2.7%. Coagulase negative staphylococci were the predominant pathogens both in sternal wound and blood stream infections. Conclusions: This study provided a data base for this cardiac center to formulate antibiotic prophylaxis and treatment guidelines. In microbiology laboratory, criteria for considering these organisms of low virulence as pathogenic were included in the standard operating procedures.